FAKTOR MATERNAL TERHADAP BERAT BADAN BAYI BARU LAHIR - Sari, Anjelina Puspita; Romlah, Romlah (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2021)
AbstractÂ Â BACKGROUND The largest contributor to the Infant Mortality Rate is LBW, in the city of Palembang the IMR has reached 29 cases with one of the causes is LBW. OBJECTIVE This study aims to determine the relationship between maternal factors and birth weight. METHODS This type of quantitative analytic research using cross sectional design. The number of samples in this study was 52 respondents. The data analysis technique used Chi-Square analysis followed by a logistic regression statistical test. RESULTS The results of the Chi-Square statistical test were the relationship between the frequency of ANC and birth weight with p-value = 0.023, there was a relationship between BMI and birth weight with p-value = 0.029, there was a relationship between LILA and birth weight with p-value = 0.003, there was a relationship between Hb and birth weight with p- value = 0.008, and there is no parity relationship with birth weight with p-value = 0.216. Based on the multivariate results, it can be seen that the variable that is most closely related to birth weight is BMI with a value of Ï value = 0.004. CONCLUSION Based on the results of this study, it is hoped that midwives can control maternal factors, so that they can reduce the incidence of LBW.Â Keywords: Birth Weight, Maternal Factor